Water-soluble distyrylbenzenes: one core with two sensory responses: turn-on and ratiometric - Tolosa, Juan; Bryant, Jonathan; Solntsev, Kyril M.; Brödner, Kerstin; Tolbert, Laren M.; Bunz, Uwe H. F. (Chemistry - a European journal, 2011)
The synthesis of four water-soluble distyrylbenzenes (compounds 1-4) is reported. Their acidochromicity in aqueous media was investigated. Blue shifts and increases in the quantum yields were observed as a general response. The pH-dependent photophysics of 1 b-3 b in water reveal unexpected protonation sequences upon titration: compound 1 b is green-yellow fluorescent at high pH (10) but becomes very weakly fluorescent between pH 5 and pH 3, whereas below pH 2 strong blue fluorescence is observed. This behavior can be explained in terms of the interplay in the protonation of aniline and of the carboxylate groups. In compound 4, a higher basicity of the amino group is observed and ratiometric fluorescence change takes place upon protonation or on reaction with zinc salts in water. Compound 4 can therefore act as a weak ratiometric zinc ligand in water, even though it has only a dimethylamino unit as a binding motif.